Back Cover: Hydrophobic Triaryl‐Substituted β‐Lactams as Activity‐Based Probes for Profiling Eukaryotic Enzymes and Host–Pathogen Interactions (ChemBioChem 15/2014). Issue 15 (13th October 2014) - Nasheri, Neda; McKay, Craig S.; Fulton, Kelly; Twine, Susan; Powdrill, Megan H.; Sherratt, Allison R.; Pezacki, John Paul
<x xml:space="preserve">Abstract</x> The back cover picture shows a β‐lactam activity‐based probe that can report on a broad range of enzyme activities at one time. This non‐directed probe captures HCV‐induced changes in the activity of mechanistically distinct enzymes that could be potential biomarkers of viral infection. For more details, see the communication by J. P. Pezacki and co‐workers on p. 2195 ff.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>